Caregiving, single parents and cumulative stresses when caring for a child with cancer. Issue 2 (2nd November 2012) - Granek, L.; Rosenberg‐Yunger, Z. R. S.; Dix, D.; Klaassen, R. J.; Sung, L.; Cairney, J.; Klassen, A. F.
Abstract Background Single parents whose children have cancer are a marginalized group who report less family centred care, and therefore, less quality cancer care for their children. As such, the aims of this study were to explore how single parents of children with cancer describe their caregiving experiences and to understand their contextual life stressors. Methods A constructivist grounded theory method was used. Qualitative interviews with 29 single parents of children with cancer who were at least 6 months post‐diagnosis were recruited between November 2009 and April 2011 from four hospitals across Canada. Line‐by‐line coding was used to establish codes and themes and constant comparison was used to establish relationships among emerging codes and conceptual themes. Results The first set of findings report on caregiving duties including: emotional tasks, informational tasks and physical tasks. The second set of findings report on the contextual picture of parent's lives including their living conditions, their physical and mental health and their family histories of disruption, trauma and disease. Conclusions Single parents caring for children with cancer were found to experience several cumulative stressors in addition to the current strain of caring for a child with cancer. The synergy of these cumulative stresses with the added strain of caregiving for a child with cancer may have long‐term health and financial implications for parents. Broad‐based policy interventions should focus on relieving the chronic strains associated with being a single parent of a child with cancer.